Pemberdayaan Pemulung Melalui Pengembangan Produk Daur Ulang dalam Meningkatkan Kemandirian Usaha dan Kesejahteraannya - Yanti , Etyca Rizky; Nardo , Rio; Mohammad , Mahatir; Aulawi, Hanif; Febrianto , Ade; Octavia , Runnisshelly (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
One of the impacts of population growth is the increase in the amount of waste produced by humans. The majority of household waste is simply thrown away and ends up in integrated waste disposal sites (TPST). One of the largest TPSTs in Indonesia is the Bantar Gebang Bekasi TPST with a land area of 110.3 hectares. This TPST is the final disposal site for waste originating from DKI Jakarta, Bekasi City and Bekasi Regency. Every day, 11,200 tons of household waste is thrown into the Bantar Gebang TPST. The rubbish was piled up into mountains. Waste that still has sales value, such as plastic waste, used tires and metal, is picked up by scavengers. The aim of this PkM activity is to improve the welfare of scavengers through developing waste recycling product businesses and increasing business independence. The implementation method used is training carried out several times. The results of implementing PkM show that scavengers who were given training experienced an increase in income. The increase in income comes from the sale of recycled waste products that they process. Sales are carried out via e-commerce so the scope of sales is very wide. Increasing the income of scavengers has an impact on improving their welfare.